Collaborative product assembly design and assembly planning : methodologies and applications - Lu, Cong, 1971- (Woodhead Publishing in mechanical engineering., 2011)
Collaborative product assembly design and assembly planning presents several newly-developed methodologies and applications for collaborative assembly design and assembly planning, two important steps during the product development life cycle. These benefits include effective and rapid assembly design and assembly planning, thereby reducing the development cost and helping manufacturers enhance profit. With increased development in computer technologies and the Internet, the traditional assembly design and assembly planning have evolved around collaborative assembly design and assembly planning to speed up the product development process. Research in this area has attracted much attention in the past decade. Based on research work in the past few years, this book will present several newly-developed methodologies and applications for collaborative assembly design and assembly planning to improve the efficiency of product development in a collaborative design environment. Provides practical and realistic solutions to engineering problemsMethodologies introduced will lead to future commercialisation of systemsDetailed step-by-step case study examples will illustrate the methodologies and be discussed thoroughly.